LEVEL OF ELECTRICITY NEED FOR 2012-2020 PT.PLN (PERSERO) INDONESIA WITH COMBINED METHODS - Lim Andi; Adi Sastra P Tarigan; Siti Anisa (Sean Institute, 2022)
Along with economic growth and population growth, the need for electricity will continue to increase. The first step that must be taken is to anticipate by forecasting the need for electrical energy in the future. This research was conducted in Indonesia to predict the demand for electrical energy in 2012-2020 using a combined method with the DKL 3.2 calculation model. Forecasts are made for 4 sectors, namely the household sector, the commercial/business sector, the industrial sector, and the general/public sector. For the overall results in Indonesia, the number of subscribers increased with an average growth of 6.23% per year from 2012-2020. Then the consumption of electrical energy will increase with an average growth of electricity consumption of 4.97% per year from 2012-2020. For connected power, the average connected power growth is 7.56% per year from 2012-2020. The total power capacity that must be prepared by PT. PLN (Persero) Indonesia in 2020 amounted to 144,678.75 kVA.